2011
DOI: 10.1029/2010jd015481
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of global precipitation data sets over the Iberian Peninsula

Abstract: [1] A new publicly available daily gridded precipitation data set over mainland Portugal is presented. This data set is also combined with a recent Spanish data set to obtain a high resolution (0.2°× 0.2°) Iberian data set, labeled IB02. This data set covers the period from 1950 to 2003 and is based on a dense network, with more than 2000 and 400 quality-controlled stations over Spain and Portugal, respectively. The ordinary kriging method, applied over Portugal for consistency with the Spanish data set, perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
147
0
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(155 citation statements)
references
References 41 publications
4
147
0
4
Order By: Relevance
“…Therefore, the use of a daily dataset, even with a smaller total number of stations, could represent an advantage to the analysis. This goal has become feasible only recently due to the merging of Spanish and Portuguese (Belo-Pereira et al, 2011), into the high density daily gridded precipitation data set "Iberia02." To a certain extent, this work provides the extension of the previous studies by the authors Cortesi et al (2013a,b), with several major changes; on the one hand, unlike the monthly regression model widely used in Cortesi et al (2013a), the analysis in this work was performed using the daily gridded "Iberia02" precipitation dataset.…”
Section: Earth Sciencementioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the use of a daily dataset, even with a smaller total number of stations, could represent an advantage to the analysis. This goal has become feasible only recently due to the merging of Spanish and Portuguese (Belo-Pereira et al, 2011), into the high density daily gridded precipitation data set "Iberia02." To a certain extent, this work provides the extension of the previous studies by the authors Cortesi et al (2013a,b), with several major changes; on the one hand, unlike the monthly regression model widely used in Cortesi et al (2013a), the analysis in this work was performed using the daily gridded "Iberia02" precipitation dataset.…”
Section: Earth Sciencementioning
confidence: 99%
“…It is based on a dense network of rain gauges, combining two national data sets, "Spain02" for peninsular Spain and Balearic islands , and "PT02" for mainland Portugal (Belo-Pereira et al, 2011), with a total of more than 2000 station over Spain and four hundred stations over Portugal, all quality-controlled and homogenized. Although the actual number of stations in any given year varies substantially due to variable availability of stations.…”
Section: Precipitation Databasementioning
confidence: 99%
See 1 more Smart Citation
“…Kidd et al (2013) found that precipitation in the tropical Atlantic is skewed to the east towards the African coast by ERA-Interim. On the other hand, several studies have shown that in the area of the Iberian Peninsula (Belo-Pereira et al, 2011) or in the area of four African river basins (Thiemig et al, 2012), ERA-Interim overestimates the frequency of rain events as well.…”
Section: Introductionmentioning
confidence: 99%
“…Herrera et al (2010aHerrera et al ( , 2010b used an extensive compilation of about 2000 daily observations in Spain to build a new daily gridded dataset, at 0.2 • × 0.2 • of horizontal resolution (latitude-longitude), for the period 1950 to March 2008. Belo-Pereira et al (2011) compiled around 400 stations and used the similar technical specifications to extend the dataset into Portugal. The merged dataset contains daily precipitation for the whole Iberian Peninsula, from 1950 to 2003, based on a dense network of rain gauges, of about 2400.…”
Section: Introductionmentioning
confidence: 99%